El lugar de la comunicación en la gestión cultural (2018)
This essay discusses about the role of the city walker and the construction of urban imaginary. Retaking the figure of the flâneur of Baudelaire, now the city walker no longer roams the gaps of capitalism, but is the one who lives hedonism and consumption. The paper discusses how city landscapes are constructed from guidebooks and cultural industry, this time used in a political manner.